Pendampingan Penyusunan RPP Berbasis Keterampilan Berpikir Kritis dan Kreatif Guru SD - Mawardi Mawardi; Wahyudi Wahyudi; Firosalia Kristin; Gamaliel Septian Airlanda (Universitas Kristen Satya Wacana Salatiga, 2021)
Learning is an activity designed by the teacher to help students find a new ability and or value. One indicator of a professional teacher is the extent to design the lessons well. The results of discussions with teachers from the Daerah Binaan 2 Korwilcam Toroh, Grobogan Regency, indicated that the teachers did not understand what, why and how to create lesson-plan based on critical and creative thinking. Based on that problem, the team conducted 1) to mentor teachers about what, why and how to create lesson-plan based on critical and creative thinking; 2) to assist the teacher in developing lesson-plan; 3) provide assistance to prepare lesson plans based on critical and creative thinking skills. Mentoring activities have been carried out on March 20-27 2021 with a number of meetings equivalent to 32 hours. The results of this mentoring is that 70.2% of elementary school teachers stated that the material presented by the resource persons was very useful for them.